Molecular systematics, taxonomy and distribution of the Pyrrhura picta-leucotis complex - Arndt, Thomas; Wink, Michael (The open ornithology journal, 2017)
Molecular systematics, taxonomy and distribution of the Pyrrhura picta-leucotis complex
Gesehen am 03.08.2017